Bridge Maintenance Strategy: Application of Bridge Condition Index (BCI) UK to Ngawi Kertasono Toll Road Bridge - Sari, Halima Irianti Puspita; Siswosukarto, Suprapto; Aminullah, Akhmad (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
In the context of toll road infrastructure, bridges are essential for connecting two distinct sections and ensure the toll road functioning properly. Therefore, to accomplish that objective and, at the same time, optimize the allocation of limited funds for maintenance, bridges require a proper maintenance priority strategy. However, in Indonesia's Bridge Management System (BMS), the importance weight of the bridge elements has not yet been used and the final result still causes bias while assembling the rankings of handling priorities. The Bridge Condition Index (BCI), developed in the United Kingdom, offers a bridge handling priority system that is determined by the importance of each bridge element. To determine the effectiveness of the BCI UK method, an analysis was carried out using the results of a visual inspection of five river bridges located on the Ngawi Kertasono toll road. According to the handling ranking result, Kedungrejo Bridge appears to be on the first rank with the dominant defect occurred on the pier element. Sukoharjo Bridge, on the other hand, has the dominant defect happened in the carriageway surfacing and is ranked last. The outcomes itself indicate that bridges with defects in critical elements, which can affect the structural stability of the bridge, will be prioritized to be repaired prior to bridges with non-structural element damages. Moreover, suitable repair recommendations can be made based on the type and severity of the damage itself. Furthermore, this result is expected to be taken into account while developing the Indonesian bridge management system in the future.